Length-dependent truncal Aδ-fiber dysfunction in hereditary transthyretin amyloidosis: An intra-epidermal electrical stimulation study - Kodaira, Minori; Ohashi, Nobuhiko; Morita, Hiroshi; Sekijima, Yoshiki (Clinical neurophysiology, 2019)
•Intra-epidermal electrical stimulation (IES) can selectively activate Aδ-fibers in the skin.•Length-dependent truncal Aδ-fiber dysfunction in ATTRm amyloidosis was demonstrated using IES.•IES may be clinically useful for investigating Aδ-fiber dysfunction at various parts of the body. To elucidate Aδ-fiber dysfunction at the trunk in patients with hereditary transthyretin (ATTRm) amyloidosis using intra-epidermal electrical stimulation (IES). In 16 patients with ATTRm amyloidosis and 18 healthy subjects, sensory thresholds using IES and cooling detection thresholds using the Computer-Aided Sensory Evaluation (CASE IV) system, were assessed to investigate Aδ-fiber functions at the Th10 level of the anterior, lateral, and posterior trunk. Furthermore, evoked potentials (EPs) following electrical stimulation using IES at the anterior and posterior trunk were evaluated. In patients with ATTRm amyloidosis, both IES and CASE IV sensory thresholds tended to be higher at the anterior trunk than at the lateral and posterior trunks. The amplitudes of EPs following electrical stimulation at the anterior trunk were lower than those at the posterior trunk. Aδ-fiber dysfunction at the anterior trunk was conspicuous in patients with more intense polyneuropathy at the limbs. In healthy subjects, there were no differences in both sensory thresholds and EP amplitudes among any examination sites. Sensory thresholds with IES and CASE IV were correlated. Evaluation using IES demonstrated length-dependent Aδ-fiber dysfunction at the trunk in patients with ATTRm amyloidosis. IES may be a useful clinical tool for investigating Aδ-fiber dysfunction at various parts of the body in patients with neuropathy.